Lovebirds in the air: trade patterns, establishment success and niche shifts of Agapornis parrots within their non-native range - Mori, Emiliano; Cardador, Laura; Reino, Luís; White, Rachel L.; Hernández-Brito, Dailos; Le Louarn, Marine; Mentil, Lorenzo; Edelaar, Pim; Pârâu, Liviu G.; Nikolov, Boris P.; Menchetti, Mattia (Biological invasions, 2019)
Understanding the factors influencing the establishment of non-native species is pivotal with regards to the development of effective biosecurity policies. In this paper, we aim to assess the role of climate matching, trade patterns and breeding origin as drivers of establishment success of introduced lovebirds (Agapornis species). A comprehensive database on the worldwide distribution of eight species of non-native lovebirds (including establishment success and population size from 21 countries spanning 27 years) was compiled. We combined climate-based species distribution models with environmental niche analyses to evaluate environmental suitability and potential niche shifts in the introduced range of lovebirds. Then, we tested whether combining habitat suitability with information on trade, introduction effort and breeding origin (captive-bred or wild-caught) of imported birds can improve model predictions at the country level. Although climate-based models fit well with the current distribution of non-native lovebirds at 5-arcminute resolution and significant niche similarity was found for 3 species, we also observed successful establishments in areas climatically distinct from those occupied in native ranges. At the country level, only a significant relationship between the number of established populations and both the number of introduction sites and the year of first importation was observed. A significant effect of breeding origin was not found, but most traded birds had a captive-bred origin. Our work contributes to the growing evidence of the complexity of the invasion process and the difficulty of pre-introduction invasion assessments based solely on the characteristics of the recipient environments for the Agapornis species. Surveillance protocols should be applied to both wild-caught and captive-bred lovebirds, as additional data becomes available to better tease apart the role of origin in those species.